Significance of mineralogy in soil mechanics - Dolinar, Bojana (Geologija, 2002)
The research of consistency limits according to Atterberg is of key importance in soil mechanics because it determines, in a simple way, results of interactions between solid and liquid phases in soils, and thus provides possibility to classify them in groups with similar mechanic properties. In most cases, the results of these investigations provide a good basis for predicting other properties such as deformability, expansion, hydraulic conductivity and strength of soils. This proves that basis factors influencing the values of consistency limits and other mechanic properties are the same. It is known that the values of consistency limits primarily depend on the type and quantity of clay minerals in soils. The article focuses on experimental evidence of dependence between the quantity of water at the liquid limit for soils and type, portion and specific surface of clay grains. Experiments were performed with monomineral soils, their mixtures and composed samples of clay- and non-clay components. It was established that in parallel orientation of clay particles the quantity of water between grains at liquid limit is dependent on their external specific surface.